Atypical presentation of acute aortic dissection in a young competitive rower. (4th September 2018) - Saunders, Tim; Suzuki, Toru
Abstract : A 27-year-old man (who is also the lead author) presented with dull pain deep to the suprasternal notch, following a period of intense exercise (rowing). He was initially sent home with no diagnosis, but 24 hours later returned to a different Accident & Emergency (A&E), due to continued discomfort and an increasingly altered mental state, and was diagnosed with an extensive type A aortic dissection extending from the aortic root to the iliac bifurcation of the aorta, with an ~8 cm aneurysm on the ascending aorta and a diseased aortic valve. Following emergency surgery to replace the aortic valve and the aorta from the aortic root to the middle of the aortic arch (hemiarch), the patient recovered well.